Antioxidant capacity of the green leafy vegetables using oxygen radical antioxidant capacity (ORAC), 2,2'-Azino-Bis (3Ethylbenzothiazoline-6-Sulphonic Acid (ABTS) and 2,2-Diphenyl-1-Picrylhydrazyl (DPPH) assays - Haron, Normah; Mat Jusoh, Hanapi (Zibeline International Publishing, 2019)
Antioxidants are believed to play a very important role in the body defence system against reactive oxygen species (ROS), the harmful by-products that are generated during normal aerobic cell respiration. The objective of this study was to determine the antioxidant capacity in green leafy vegetables using ORAC, ABTS, and DPPH assays of different polyphenol fractions (free phenolic, alkaline hydrolysate, acidic hydrolysate).The antioxidant capacity of the identified free and bound phenolic acid content was measured using different assays including ORAC, ABTS, and DPPH assay (end-point assay and kinetic assay). Only hydrophilic antioxidant activities of all selected samples were examined using ORAC assay. Strong correlations were observed in acidic and alkaline hydrolysate fractions (p<0.01) as determined by ORAC and ABTS assays, respectively. In the free phenolic acid extracts, the O. basilicum (Sweet basil) ranked first, had highest antioxidant capacities of 521804±4243 µmol TE/100g DW, 329.8±0.4mg TE/g DW and 9.0±1.8 µg GAE/g DW as determined by ORAC, ABTS and DPPH, respectively. . The A. occidentale (Cashew shoot) in the alkaline hydrolysate extract showed a greatest antioxidant capacity in all three assays: 889126±7193 µmol TE/100g DW, 466.5±7.9 mg TE/g DW and 3.5±0.4 µg GAE/g DW as measured by ORAC, ABTS and DPPH, separately. While, in acidic hydrolysate, the A. occidentale (Cashew shoot) extract also dominated the antioxidant capacity with (560504±5785 µmol TE/100g DW, 387±0.7 mg TE/g DW and 5.9±0.5 µg GAE/g DW) as determined by ORAC, ABTS and DPPH assays, respectively. The acidic and basic hydrolysis yielded higher antioxidant capacities in the present study. It suggests that hydrolysis with alkaline and acidic play significant roles in liberating more phenolic acids and flavonoids and generating high antioxidant capacity in the extracts.